Migration meets Bildung: Jenny Erpenbeck’s Go, Went, Gone - Lilla Balint; Landon Reitz (Studies in 20th & 21st Century Literature, 2022)
At the time of its publication, German writer Jenny Erpenbeck’s novel Go, Went, Gone (2017; Gehen, Ging, Gegangen, 2015) was hailed for its particular timeliness, as its story revolves around the most recent influx of asylum seekers and refugees from African to European countries, including Germany. In contradistinction to readings of Go, Went, Gone as a narrative of migration, our article places the novel in the tradition of the bildungsroman and takes Erpenbeck’s choice of protagonist as its starting point: in asking what is rendered visible through the privileged perspective of Richard—a recently retired classics professor—we argue that Erpenbeck’s novel reckons with the colonial underpinnings of western epistemology, the fundamental Eurocentrism of Bildung and its established narrative, and their effects on German political and social attitudes toward migration. As a bildungsroman with an aging protagonist, Go, Went, Gone renders migration as the consequence of European modernity and colonialism.
Keywords: bildungsroman; migration; colonialism; decoloniality; age